Depressive Emotion Detection and Behavior Analysis of Men Who Have Sex With Men via Social Media - Li, Yong; Cai, Mengsi; Qin, Shuo; Lu, Xin (Frontiers in Psychiatry, 2020)
Background: A large amount of evidence has indicated an association between depression and HIV risk among men who have sex with men (MSM), but traditional questionnaire-based methods are limited in timely monitoring depressive emotions with large sample sizes. With the development of social media and machine learning techniques, MSM depression can be well monitored in an online and easy-to-use manner. Thereby, we adopt a machine learning algorithm for MSM depressive emotion detection and behaviour analysis with online social networking data. Methods: A large-scale MSM dataset including 664,335 users and over 12 million posts was collected from the most popular MSM-oriented geosocial networking mobile application named Blued. Also, a non-MSM Benchmark dataset from Twitter was used. After data preprocessing and feature extraction of these two datasets, a machine learning algorithm named XGBoost was adopted for detecting depressive emotions. Results: The algorithm shows good performance in the Blued and Twitter datasets. And three extracted features significantly affecting the depressive emotion detection were found, including depressive words, LDA topic words, and post-time distribution. On the one hand, the MSM with depressive emotions published posts with more depressive words, negative words and positive words than the MSM without depressive emotions. On the other hand, in comparison with the non-MSM with depressive emotions, the MSM with depressive emotions showed more significant depressive symptoms, such as insomnia, depressive mood, and suicidal thoughts. Conclusions: The online MSM depressive emotion detection using machine learning can provide a proper and easy-to-use way in real-world applications, which help identify high-risk individuals at the early stage of depression for further diagnosis.